Integration of Mobile Interaction Technology in the Tourism Industry and Its Impact on Tourism Consumption Patterns - Jin, Huihui (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The introduction of mobile interaction technology has fundamentally transformed the delivery of tourism services, enabling travelers to access real-time information, engage in online interactions, and enjoy personalized services through smart devices. This innovative consumption model not only enhances tourist engagement and satisfaction but also drives innovation and transformation in the tourism industry. However, despite existing studies exploring the impact of technology on tourism, most research focuses primarily on the technology itself, lacking a systematic analysis of its deeper implications for reshaping consumption patterns, enhancing industry resilience, and addressing market uncertainties. Current studies are predominantly centered on applications related to big data and consumer behavior analysis, often overlooking how to measure the resilience of tourism consumption patterns through specific indicators and failing to investigate the long-term sustainability of consumption models transformed by interactive technologies. To address these research gaps, this study introduces a novel perspective by constructing a mobile interaction network model, defining resilience indicators for tourism consumption patterns, and systematically evaluating them using a comprehensive assessment approach. This study aims to provide a new theoretical framework for the digital transformation of the tourism industry and practical guidance for enhancing industry resilience and improving risk resistance capabilities.